Recent warming and increasing CO2 stimulate growth of dominant trees under no water limitation in South Korea - Arco Molina, Julieta Gabriela; Saurer, Matthias; Altmanova, Nela; Treydte, Kerstin; Dolezal, Jiri; Song, Jong-Suk; Altman, Jan (Tree physiology, 2024)
Increases in temperatures and atmospheric CO2 concentration influence the growth performance of trees worldwide. The direction and intensity of tree growth and physiological responses to changing climate do, however, vary according to environmental conditions. Here we present complex, long-term, tree-physiological responses to unprecedented temperature increase in East Asia. For this purpose, we studied radial growth and isotopic (δ13C and δ18O) variations using tree-ring data for the past 100 yr of dominant Quercus mongolica trees from the cool-temperate forests from Hallasan, South Korea. Overall, we found that tree stem basal area increment, intercellular CO2 concentration and intrinsic water-use efficiency significantly increased over the last century. We observed, however, short-term variability in the trends of these variables among four periods identified by change point analysis. In comparison, δ18O did not show significant changes over time, suggesting no major hydrological changes in this precipitation-rich area. The strength and direction of growth-climate relationships also varied during the past 100 yr. Basal area increment (BAI) did not show significant relationships with the climate over the 1924-1949 and 1975-1999 periods. However, over 1950-1974, BAI was negatively affected by both temperature and precipitation, while after 2000, a temperature stimulus was observed. Finally, over the past two decades, the increase in Q. mongolica tree growth accelerated and was associated with high spring-summer temperatures and atmospheric CO2 concentrations and decreasing intrinsic water-use efficiency, δ18O and vapour pressure deficit, suggesting that the photosynthetic rate continued increasing under no water limitations. Our results indicate that the performance of dominant trees of one of the most widely distributed species in East Asia has benefited from recent global changes, mainly over the past two decades. Such findings are essential for projections of forest dynamics and carbon sequestration under climate change.
Keywords: stomatal conductance; Climate Change; izotopy uhlíku; Korejská republika; teplota; klimatické změny; Republic of Korea; intrinsic water-use efficiency; Carbon Isotopes; climate change; dub (rod); Carbon Dioxide; Oxygen Isotopes; stromy; Quercus; voda; Temperature; Water; izotopy kyslíku; oxid uhličitý; photosynthetic rate; tree-ring width; stable isotopes; Trees